Better leveraging monetary rewards in the 21st century workplace using Self-Determination Theory - Anaïs Thibault Landry; Konstantinos Papachristopoulos; Yu-Shan Hsu; Yu-Ping Chen (International Journal of Business Science & Applied Management (IJBSAM), 2022)
The purpose of this article is to understand how to better leverage monetary rewards at work using Self-Determination Theory (SDT). According to SDT research, employees can ascribe different functional meaning to monetary rewards. When rewards take on an informative meaning, they positively contribute to employees' basic psychological needs, leading to greater autonomous motivation, and better work outcomes, while when presented in a coercive way they negatively contribute to employees' basic psychological needs because they lead to greater controlled motivation. We propose that employers need to better understand employees' attributes, consider alternative forms of rewards and provide communication training, in order to better satisfy employees' psychological needs and avoid the negative outcomes of controlling monetary rewards. Our research contributes to the understanding of both employers' and employees' experience of workplace cash rewards and explores theoretical avenues on how rewards in modern work contexts need to be functionally contextualized by personal, organizational and cultural factors (e.g., the functional meaning of rewards, basic needs satisfaction).
Keywords: 650; self-determination theory; meaning of monetary rewards; psychological needs; motivation; work outcomes